Investigation of dust pollutants and the impact of suspended particulate matter on the performance of photovoltaic systems - Tamoor, Muhammad; Hussain, Muhammad Imtiaz; Bhatti, Abdul Rauf; Miran, Sajjad; Arif, Waseem; Kiren, Tayybah; Lee, Gwi Hyun (Frontiers in Energy Research, 2022)
The purpose of this study is to investigate the potential of airborne particulate matter (PM10, PM2.5) and its impact on the performance of the photovoltaic (PV) system installed in the Sargodha region being affected by the crushing activities in the hills. More than 100 stone-crushers are operating in this region. The four stations within this region are selected for taking samples during the summer and winter seasons. Glass-fiber papers are used as a collection media for particulate matter (PM) in high volume sampler. The concentration of PM is found above the permissible limit at all selected sites. The chemical composition, concentration and the formation of the particulate matter (PM10, PM2.5) layers on the surface of the photovoltaic module varies significantly depending on the site location and time. The accumulation of PM layers on PV modules surface is one of the operating environmental factors that causes significant reduction in PV system performance. Consequently, it leads to power loss, reduction of service life and the increase in module temperature. For the PV system’s performance analysis, two PV systems are installed at the site having higher PM concentration. One system is cleaned regularly while the other is kept dusty. The data of both PV systems are measured and compared for four months (two months for summer and two for winter season). It is found that, when the level of suspended particulate matter (PM10, PM2.5) increases, the energy generation of dusty PV system (compared to the cleaned one) is reduced by 7.48% in May, 7.342% in June, 10.68% in December, and 8.03% in January. Based on the obtained results, it is recommended that the negative impact of PM on the performance of PV system should be considered carefully during the decision-making process of setting solar energy generation targets in the regions with high level of particulate matter.